Gathering Linguistic Data from Multinational Companies: Inter-Cultural Communication in the Workplace - Briguglio, Carmela (2016)
That much communication in international business, particularly in multinational companies, takes place in English, is a fact that faces little challenge. English is increasingly a global language, with estimates that nearly one quarter of the world’s population, or between 1.2 and 1.5 billion people, are already fluent or competent in it (Crystal, 1997). This trend is likely to continue in the foreseeable future (Crystal, 2012; Graddol, 2000 & 2006), and in the field of business, arguably even more so than in other areas (Bargiela-Chiappini & Nickerson, 2003; LouhialaSalminen & Charles, 2006). Economic developments on a global scale, new communications technologies, the explosion in international marketing and advertising, and mass entertainment have also promoted the continued expansion of English as a global “lingua franca”.